Enteric opportunistic parasites in HIV positive patients and associated risk factors - Varghese, Ann Maria; Harbade, Mangala S.; Iravane, Jyoti A. (International Journal of Research in Medical Sciences, 2025)
Background: Depletion of CD4+ T-cells following HIV infection leads to immune system collapse, leaving patients susceptible to opportunistic infections. In developing countries like India, parasites cause diarrhoea in over 90% of HIV patients. This study was conducted to identify the enteric opportunistic parasitic diseases that affect HIV-positive patients and associated risk factors. This study also focuses on the identification of Cryptosporidium species by conventional methods and comparing them with ELISA. Methods: A cross-sectional study was carried out in the Department of Microbiology, GMCH, Aurangabad, from January 2023 to June 2024. Total 104 stool samples of HIV-positive patients were collected. Proper history was obtained to identify the risk factors. The samples were subjected to direct wet mount, concentrated using formalin-ether method, followed by modified Ziehl-Neelsen staining, Auramine O fluorescent staining, and ELISA. Results: The parasites identified include Cryptosporidium (34), Cyclospora cayetanensis (1), Strongyloides stercoralis (1), and Entamoeba (1). The risk factors associated with opportunistic infections were high HIV viral load, low CD4 count, shorter duration of ART, chronic diarrhea, and occupation. Auramine O staining was identified as superior to wet mount and modified Ziehl-Neelsen staining for identification of Cryptosporidium spp. Conclusions: Clinicians can fight AIDS more successfully with proper knowledge about opportunistic infections. Since the spectrum of opportunistic infections varies with geography, their pattern in a particular area is of utmost importance. Understanding the risk factors and optimal diagnostic techniques for opportunistic infections helps in prompt treatment, contributing to delaying the progression to AIDS.